Odpowiedzi

2010-04-13T16:01:35+02:00
-1/4 * (2 + x) = 3/4x
-1/4 * 2 - 1/4 * x = 3/4x
-0,5 - 1/4x = 3/4x
-0,5 = 3/4x + 1/4x
-0,5 = 4/4x
x = (-0,5)

-2 * (x + 1/2) - 3 * (x + 1/3) = 0
-2x - 1 - 3x - 1 = 0
-5x - 2 = 0
-5x = 0 + 2
-5x = 2
x = 2 : (-5)
x = (-0,4)

(x + 2) ∧ 6 = 0,5x
6x + 12 = 0,5x
12 = 0,5x - 16x
12 = (-15,5x)
x = 12 : (-15,5)
x = (-24/31)

0,1 * (x + 2) = 0,2x
0,1x + 0,2 = 0,2x
0,2 = 0,2x - 0,1x
0,2 = 0,1x
x = 0,2 : 0,1
x = 2

6 * (1 - 1/3x) = 2 * (1 + 1/2x)
6 - 2x = 2 + x
-2x - x = 2 - 6
-3x = (-4)
x = (-4) : (-3)
x = 1 1/3